Short‐Period Concentric Traveling Ionospheric Disturbances Excited by the Launch of China's Long March 4B Rocket Detected by 1 Hz GNSS Data - Xiaolin Li; Feng Ding; Xinan Yue; Jianyong Li (Space Weather)
Abstract Using high‐resolution global navigation satellite system data with a temporal resolution of 1 s, we presented observations of short‐period concentric traveling ionospheric disturbances (CTIDs) triggered by the launch of the Long March 4B rocket at 03:26 UT 7 December 2014 in Taiyuan, China. The total electron content (TEC) perturbations observed approximately 22 min after the launch have amplitudes of ∼0.1–0.3 TEC units, horizontal phase velocities of ∼832–1,348 m/s, and durations of ∼600 s. With periods of ∼90–200 s, these disturbances are the shortest‐period TIDs excited during rocket launches reported thus far. The CTIDs began with a quick increase in the amplitude, followed by 5–6 periodic oscillations with decreasing amplitude. A continuous southward propagation of 5 wave fronts was observed, which propagated southward at a distance of ∼450 km in 600 s. A slow decrease in perturbation amplitude during propagation was found. According to the direction of horizontal velocity observed by different stations, we found that the source region of the CTIDs was located ∼140 km south of the launch site. The CTIDs were most likely generated after the ignition of second‐stage rockets above the mesopause region.